Learning-based personalisation of robot behaviour for robot-assisted therapy - Stolarz, Michał; Mitrevski, Alex; Wasil, Mohammad; Plöger, Paul G. (Frontiers in Robotics and AI, 2024)
During robot-assisted therapy, a robot typically needs to be partially or fully controlled by therapists, for instance using a Wizard-of-Oz protocol; this makes therapeutic sessions tedious to conduct, as therapists cannot fully focus on the interaction with the person under therapy.In this work, we develop a learning-based behaviour model that can be used to increase the autonomy of a robot's decision-making process. We investigate reinforcement learning as a model training technique and compare different reward functions that consider a user's engagement and activity performance. We also analyse various strategies that aim to make the learning process more tractable, namely (i) behaviour model training with a learned user model, (ii) policy transfer between user groups, and (iii) policy learning from expert feedback. We demonstrate that policy transfer can significantly speed up the policy learning process, although the reward function has an important effect on the actions that a robot can choose. Although the main focus of this paper is the personalisation pipeline itself, we further evaluate the learned behaviour models in a small-scale real-world feasibility study in which six users participated in a sequence learning game with an assistive robot. The results of this study seem to suggest that learning from guidance may result in the most adequate policies in terms of increasing the engagement and game performance of users, but a large-scale user study is needed to verify the validity of that observation.